‘Still there’: mediating personhood, temporality, and care in London Alzheimer’s Society support groups - Kennedy, Lilian Elisabeth (The University of Edinburgh, 2019)
This thesis is an investigation of the lives of people living with dementia and their families to explore how and why the ‘social death’ of the disease is mitigated through everyday practices of care. Findings are based on informal interviews and research done within London Alzheimer's Society services, in particular support groups for familial carers and support groups for people with dementia. One of the primary concerns of my interlocutors was keeping a person with dementia in temporal and spatial synchronicity with the rhythms and routines of family life. This was a challenge in the face of progressive dementia symptoms that disrupted people’s ability to make sense of time and to navigate space. I show that staying ‘in synchrony’ is directly linked to constructions of relational embeddedness and independence, and is at the heart of familial care practices aimed at keeping a person with dementia ‘still there.’ My interlocutors’ construction of personhood relies on a delicate balance of interdependence in which connection to kin is encouraged, but also carefully negotiated so that autonomy is protected, and people do not lapse into explicit dependence. In the contexts of dementia, independence is a relationally constructed project, and relationality requires distinction and separation between people. I argue further that my interlocutors sought to maintain a person with dementia’s personhood by finding ways for them to recognize and to reciprocate the care that they are given. In line with this, embodied forms of communication and behaviour previously considered ‘odd’ because they were inappropriate to the time and place came to be seen as meaningful. In my interlocutors’ practices, we can see that care can be both constitutive of kinship and individuality, as well as a threat to it. Thus, my research is situated within anthropological studies that show the importance of both kinship and autonomy for Western personhood.
Keywords: dementia; lived experience; carers; Alzheimer's disease; temporality; kinship; care